PARAPHIMOSIS IN A CASTRATED BUCK - S. Prakash; D. Alfeena Nancy; S. Satheshkumar; P. Jayaganthan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 2-years-old non-descript buck was presented with a protruded penis with dribbling of urine. Based on the clinical signs the condition was diagnosed as paraphimosis. The buck was treated and resulted in successful correction without recurrence. This case describes the management of paraphimosis in a buck .